Some important aspects of vehicle modeling: Suspensions and tires. (Mechanics Class) - Pires Vaz, Emanuel Eduardo (2020)
The study of seats, and tires for the vehicle market aims at a mechanics class for the FEUP and ISEP car courses. Other important aspects, taking into account the ground, are interpreted here in a simple military vehicle.Two problems are presented: the first on the seat functionalities, through the mechanical study done by electrical duality; and the second through the study of the ropes of the tire wire screens.